1982
DOI: 10.1159/000272812
|View full text |Cite
|
Sign up to set email alerts
|

Competence, Contingency, and the Development of Perceived Control

Abstract: In an effort to learn how perceived internal control changes with age, 33 developmental studies using 12 different locus of control (LOC) scales are surveyed. A few studies show developmental declines in perceived control, about half show consistent developmental increases, and about half show mixed results or no significant developmental differences. A critical examination of the LOC scales reveals that some developmental findings may be artifacts of scale characteristics, and that others may reflect developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
134
1
7

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(149 citation statements)
references
References 84 publications
(91 reference statements)
7
134
1
7
Order By: Relevance
“…Studies of the relations between individual control beliefs and achievement (e.g., grades and test scores) or self-regulation (e.g., study effort and strategies) in academic settings, have generally shown that higher levels of both achievement and self-regulation are positively related to higher self-efficacy, more internal locus of control, causal attribution of success to internal causes such as effort and ability, and higher outcome expectancy and are negatively related to causal attribution of success to external causes such as luck and task difficulty (e.g., see reviews in Bandura, 1986Bandura, , 1993Stipek, 1993;Stipek & Weisz, 1981;Weiner, 1986;Wigfield & Eccles, 1992). The relations identified generally correspond to those that would be expected based on the various theoretical formulations of control (e.g., Bandura, 1986;Ford & Thompson, 1985;Heckhausen & Schulz, 1995;Rotter, 1966;Skinner et al, 1988;Weiner, 1966;Weisz & Stipek, 1982). However, there have been exceptions to these patterns of relationship, particularly for causal attributions (e.g., Platt, 1988;Vispoel & Austin, 1995).…”
Section: Analysis Of the Relations Between Control Beliefs And Achievmentioning
confidence: 61%
See 2 more Smart Citations
“…Studies of the relations between individual control beliefs and achievement (e.g., grades and test scores) or self-regulation (e.g., study effort and strategies) in academic settings, have generally shown that higher levels of both achievement and self-regulation are positively related to higher self-efficacy, more internal locus of control, causal attribution of success to internal causes such as effort and ability, and higher outcome expectancy and are negatively related to causal attribution of success to external causes such as luck and task difficulty (e.g., see reviews in Bandura, 1986Bandura, , 1993Stipek, 1993;Stipek & Weisz, 1981;Weiner, 1986;Wigfield & Eccles, 1992). The relations identified generally correspond to those that would be expected based on the various theoretical formulations of control (e.g., Bandura, 1986;Ford & Thompson, 1985;Heckhausen & Schulz, 1995;Rotter, 1966;Skinner et al, 1988;Weiner, 1966;Weisz & Stipek, 1982). However, there have been exceptions to these patterns of relationship, particularly for causal attributions (e.g., Platt, 1988;Vispoel & Austin, 1995).…”
Section: Analysis Of the Relations Between Control Beliefs And Achievmentioning
confidence: 61%
“…In current conceptualizations of control, perception of whether one is capable of exerting control is thought to arise from an integration of self-efficacy, attribution, and expectancy beliefs (e.g., see Ford & Thompson, 1985;Heckhausen & Schulz, 1995;Skinner, Chapman, & Baltes, 1988;Weisz & Stipek, 1982). Most of the previous research, however, has examined expectancy, causal attribution, and self-efficacy beliefs separately or has examined the independent effects of these beliefs in regression or path analysis (e.g., see reviews in Bandura, 1986Bandura, , 1993Stipek, 1993;Stipek & Weisz, 1981;Weiner, 1986;Wigfield & Eccles, 1992).…”
Section: Analysis Of the Relations Between Control Beliefs And Achievmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the question arises as to how past feelings of perceived control can affect present psychological and physical health of the elderly. Perhaps perceived control at different times throughout the lifespan gives a sense of an ability to determine the shape of one's life (Weisz & Stipek, 1982). Or perhaps simply reviewing one's life and looking back positively on undesirable events as a result of perceived control at that time can have beneficial effects on one's psychological health in old age.…”
Section: Discussionmentioning
confidence: 99%
“…Mais especificamente, duas importantes dimensões da percepção de controlo que, ao não serem diferenciadas, poderão dificultar a interpretação dos dados empíricos existentes são, de um lado, a Percepção de Contingência de resultados e, de outro, a Percepção de Competência do Eu (Weisz, 1983;Weisz & Stipek, 1982;Skinner, 1996;Skinner & Connel, 1986). Se é certo que outros autores já haviam ressaltado a importância desta distinção (ex., Bandura, 1977;Weisz, 1983;Weisz e Stipek, 1982), ela foi retomada por Ellen Skinner que, num esforço de integração de uma literatura divergente, avançou um modelo integrador dos vários constructos relativos ao controlo (Skinner, 1995(Skinner, , 1996Skinner et al, 1988a).…”
Section: Fundamentação Teóricaunclassified